Enhancing pressure ulcer prevention using wound dressings: what are the modes of action?. Issue 4 (30th July 2013) - Call, Evan; Pedersen, Justin; Bill, Brian; Black, Joyce; Alves, Paulo; Brindle, C. Tod; Dealey, Carol; Santamaria, Nick; Clark, Michael
Abstract Recent clinical research has generated interest in the use of sacral wound dressings as preventive devices for patients at risk of ulceration. This study was conducted to identify the modes of action through which dressings can add to pressure ulcer prevention, for example, shear and friction force redistribution and pressure distribution. Bench testing was performed using nine commercially available dressings. The use of dressings can reduce the amplitude of shear stress and friction reaching the skin of patients at risk. They can also effectively redirect these forces to wider areas which minimises the mechanical loads upon skeletal prominences. Dressings can redistribute pressure based upon their effective Poisson ratio and larger deflection areas, providing greater load redistribution.